Equivalence of Definitions of Normal Subset/3 and 4 imply 2

From ProofWiki
Jump to navigation Jump to search

Theorem

Let $\left({G,\circ}\right)$ be a group.

Let $S \subseteq G$.

Let $S$ be a normal subset of $G$ by Definition 3 and Definition 4.


Then $S$ is a normal subset of $G$ by Definition 2.


Proof

By Equivalence of Definitions of Normal Subset: 3 iff 4, $S$ being a normal subset of $G$ by Definition 3 and Definition 4 implies that the following hold:

$(1)\quad \forall g \in G: g \circ S \circ g^{-1} \subseteq S$
$(2)\quad \forall g \in G: g^{-1} \circ S \circ g \subseteq S$
$(3)\quad \forall g \in G: S \subseteq g \circ S \circ g^{-1}$
$(4)\quad \forall g \in G: S \subseteq g^{-1} \circ S \circ g$

By $(1)$ and $(3)$ and definition of set equality:

$\forall g \in G: g \circ S \circ g^{-1} = S$

By $(2)$ and $(4)$ and definition of set equality:

$\forall g \in G: g^{-1} \circ S \circ g = S$

$\blacksquare$